Pengaruh Praktek Manajemen Keuangan dan Inovasi Terhadap Kinerja Keuangan Usaha Mikro Kecil Menengah Selama Masa Pandemi Covid-19 di Kota Depok - Synta Dewi Cania; Laela Susdiani (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2021)
The purpose of this study is to determine the effect of financial management practices and innovations to company’s performance on micro, small and medium enterprise during the Covid-19 pandemic in Depok City. The sampling of this study used the slovin’s formula and obtained a sample of 100MSMEs in Depok City. The data analyze used is multiple regression by used the SPSS program version 25. The results of this study indicate that financial management practices and product innovation has influence on company’s performance. While process innovation, marketing innovation and organizational innovation has no influence on company’s performance. Keywords: Financial Management Practices, Innovations, Company’s Performance, UMKM (micro, small, and medium enterprise)